Identification of Genomic Insertion and Flanking Sequence of G2-EPSPS and GAT Transgenes in Soybean Using Whole Genome Sequencing Method - Guo, Bingfu; Guo, Yong; Hong, Huilong; Qiu, Li-Juan (Frontiers in Plant Science, 2016)
Molecular characterization of sequences flanking exogenous fragment insertions is essential for safety assessment and labeling of genetically modified organisms (GMO). In this study, the T-DNA insertion sites and flanking sequences were identified in two newly developed transgenic glyphosate-tolerant soybeans GE-J16 and ZH10-6 based on whole genome sequencing (WGS) method. About 21 Gb sequence data (~21× coverage) for each line was generated on Illumina HiSeq 2500 platform. The junction reads mapped to boundary of T-DNA and flanking sequences in these two events were identified by comparing all sequencing reads with soybean reference genome and sequence of transgenic vector. The putative insertion loci and flanking sequences were further confirmed by PCR amplification, Sanger sequencing, and co-segregation analysis. All these analyses supported that exogenous T-DNA fragments were integrated in positions of Chr19: 50543767-50543792 and Chr17: 7980527-7980541 in these two transgenic lines. Identification of the genomic insertion site of the G2-EPSPS and GAT transgenes will facilitate the use of their glyphosate-tolerant traits in soybean breeding program. These results also demonstrated that WGS is a cost-effective and rapid method of identifying sites of T-DNA insertions and flanking sequences in soybean.